Blind Spots, Biases, and Other Pathologies in the Boardroom - Merchant, Kenneth A (Business Expert, 2012)
Corporate governance is one of the hottest topics in the business world now, as it always is in times of stress. Some of the recently discovered scandals and corporate failures can be traced back to corporate governance failures. Boards of directors must share some of the blame in many of the failures. Something was not working right, even in some boardrooms full of highly qualifi ed individuals. Boards have been criticized for being too large or too small, for having members who are not independent or who lack the requisite knowledge, or for enabling “bad apple” directors who are inattentive, weak, and even self-serving, among other things. But that is not at all what this book is about. In this book we show how seemingly ideal boards, those with “best practice” size, composition, and structure, can still fail to provide good governance simply because they fall victim to problems inherent in all groups. While having groups of board members provide corporate oversight is probably necessary, and even advantageous in some respects, groups have a dark side too. Tendencies that occur in group behavior can destroy or obscure the talents of even highly intelligent, energetic, and wellintended individuals, causing collective blind spots, biases, and ineffi - ciencies that can render boards ineffective. Groups often perceive risks differently from the way individual group members do and collectively fail to see problems where they really exist. Groups tend toward conformity in perceptions and attitudes, even when they are obviously wrong. Groups are prone to framing decisions in ways that none of the good decision makers on the board would do individually. And groups often waste time on unimportant details both when more important activities await and when meeting time is severely limited. No group is immune to these destructive patterns, which makes understanding them critically important from a governance standpoint. They can impair board effectiveness even when all the right pieces (and people) are in place. In this book we argue that as a fi rst step it is important to recognize these group dynamics and the problems they cause. Some of them can be minimized through, for example, properly designed decision processes.Others are more complicated. But all of them need to be recognized and understood so that we can properly shape our expectations of the degree and quality of oversight corporate boards of directors can provide and so that we can turn our energy toward the many group-level factors that could improve board performance going forward. This book is intended for board members, managers, and advanced students who want to further their knowledge of boardroom behavior and, particularly, the negative effects that are produced by common boardroom dynamics. The readers of this book will benefi t by becoming aware of these potentially serious problems, possible remedies, and tradeoffs that must be made.